An Assessment of Soil Available Nutrients Status of Chunar Area in Mirzapur District of Eastern Uttar Pradesh - Singh* and Sreejan Singh, Lalit Pandey, Amit Prajapati, Surendra (Journal of the Indian Society of Soil Science, 2021)
Present investigation was conducted to assess the physicochemical properties as well as available nutrients status of alluvial soils of Chunar area in Naryanpur block of Mirzapur district of eastern part of Uttar Pradesh. Naryanpur block has total net sown area of 17376 hectares. Altogether, ninety-eight surface soil samples were collected from the farmer’s field of Chunar area covering eleven villages. The analysis of the soil samples revealed that majority of the soil samples fall under sandy clay loam to sandy loam. The soils were slightly acidic to moderately alkaline in reaction ranging from pH 6.3-8.9 with a mean pH value of 8.03. The EC value ranged from 0.12 dS m-1 to 0.89 dS m-1 with a mean value of 0.30 dS m-1. Mean value of organic carbon (OC) was 4.6 g kg-1 and varied from 1.6-12.7 g kg-1, CaCO3 content varied from 0.08 to 3.4% with mean value of 1.05%. Mean values for nitrogen (N), phosphorus (P) and potassium (K) as obtained from the analysis were 229, 24.4, 232 kg ha-1, respectively. Overall, mean values for exchangeable Ca and Mg and available S were 14.5, 3.84 cmol(p+)kg-1 and 10.7 mg kg-1, respectively. The mean values for available Cu, Mn, Fe, Zn and B were 0.74, 4.99, 20.8, 0.85 and 0.43 mg kg-1, respectively. Available N, S and B were rated to be low in soils. Hence, there is need to supply these deficient nutrients through external organic and inorganic sources for sustaining crop productivity and soil health of Chunar area in Narayanpur block of Mirzapur district of eastern Uttar Pradesh.